Exercise Physiology / Theory and Application to Fitness and Performance: Sixth Edition - Howley Edward T; Powers Scott K (Mcgraw Hill, 2007)
Physiology of Exercise, Physiology of Exercise in the United States - Its Past and Its Future, Control of the Internal Environment, Bioenergetics, Exercise Metabolism, Hormonal Responses to Exercise, Measurement of Work and Power and Energy Expenditure, The Nervous System: Structure and Control of Movement, Skeletal Muscle: Structure and Function, Circulatory Responses to Exercise, Respiration During Exercise, Acid-Base Balance During Exercise, Temperature Regulation, The Physiology of Training: Effect on VO2 Max and Performance and Homeostasis and Strength, Physiology of Health and Fitness, Patterns in Health and Disease: Epidemiology and Physiology, Work Tests to Evaluate Cardiorespiratory Fitness, Exercise Prescriptions for Health and Fitness, Exercise for Special Populations, Body Composition and Nutrition for Health, Physiology of Performance, Factors Affecting Performance, Laboratory Assessment of Human Performance, Training for the Female Athlete and Children and Special Populations, Nutrition and Body Composition and Performance, Exercise and the Environment, Ergogenic Aids.